Corporate Criminal Liability - Priambodo, Putra Aji Widia; Nugraha, Dakha Hadi; Susila, M. Endriyo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
In the development of economic globalization, crimes committed by business actors in the form of companies in the economic field can cause losses and can also cause victims, and are supported by the emergence and development of science and information technology. This study aims to find out the rules and regulations that can ensnare in the case of corporations as legal entities and to be able to distinguish directors as personalities who are responsible for corporate crimes and directors as asset managers in corporations if there is corporate crime. Crime can be identified by the occurrence of losses that result in criminal liability, which until now still invites debate, how is this corporate responsibility considering that in the Indonesian Criminal Code, which is considered a subject of criminal law is an individual in the biological sense who In addition to that, the Criminal Code adheres to the principle of Sociates Delequere non Potest where legal entities or corporations are deemed unable to commit a crime.